Intégration européenne et déclin du néo-corporatisme. Un renversement de perspective à la lumière des accords collectifs sur la formation continue - Étienne Cognard (Revue de la Régulation)
In this article, we show that the European integration and the globalisation may be under certain circumstances a factor of development of a neo-corporatism. To achieve this conclusion we propose a historical institutionalist analysis of corporatist funds for further training and of their emergence over the past three decades. The bipartite funds can be interpreted as the result of cross-class coalitions between trade unions and employer organisations researching legitimacy towards employees and SMEs. More than these actors, multinationals have been the beneficiaries of European integration. The setting up of training funds in Europe appears then as an inter-class response of the losers of European economies’ opening to the constraints it engenders.